Going native, going home. Ethnographic empathy and the artifice of return in Cabeza de Vaca’s Relación. - Jáuregui, Carlos A. (Colonial Latin American Review, 2016)
An essay is presented which argues that Spanish soldier and explorer Álvar Núñez Cabeza de Vaca's book "Relación" does not fully tell the story of an unarmed benevolent conquistador. It proposes that the book counters instabilities with a continuous display of ethnographic distancing and an obstinate imperial teleology of return that over-codifies the journey's narrative by the author.